Subthalamic nucleus deep brain stimulation evokes resonant neural activity - Sinclair, N; McDermott, H; Bulluss, K; Fallon, J; Perera, T; Xu, S; Brown, P; Thevathasan, W (Wiley, 2018)
Deep brain stimulation is a rapidly expanding treatment for neurological and psychiatric conditions; however, a target-specific biomarker is required to optimize therapy. Here we show that deep brain stimulation evokes a large-amplitude resonant neural response focally in the subthalamic nucleus. This response is greatest in the dorsal region (the clinically optimal stimulation target for Parkinson’s disease), coincides with improved clinical performance, is chronically recordable, and present under general anesthesia. These features make it a readily utilizable electrophysiological signal that could potentially be used for guiding electrode implantation surgery and tailoring DBS therapy to improve patient outcomes.